Paleomagnetic studies on the lava pile between Skálavík and Álftafjörður, Northwest Iceland (Dataset) ... - Kristjánsson, Leó (Magnetics Information Consortium (MagIC), 2023)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Paleomagnetic studies on the lava pile between Skálavík and Álftafjörður, Northwest Iceland ...